The Effect STEAM Based Discovery Learning Model on Students Thinking Ability: Meta-Analysis Study - Dalimawaty Kadir; Loso Judijanto; Joko Widodo; Effi Alfiani Sidik; Muhammad Syahidul Haq; Tomi Apra Santosa (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of the STEAM-based discivery learning model on students' critical thinking skills. This research is a type of meta-analysis research. The researchsample came from 17 national and international journals. Samples were obtained through databases in the journals Springer, Wiley, ScienceDirect, Google Scholar, Taylor of Francis, SAGE, and the Education Resources Information Center (ERIC). The inclusion criteria are research published in 2019-2023; The study had experimental and control classes, journals had to be indexed Science and Technology Index (SINTA), Scopus, and Web of Science (WOS) and the sample size in this study was 1,078 students. Data analysis calculated the value of summary effect size, heterogeneity test and publication bias with JASP 0.8.0.4 application.Â  These results conclude that the summary effect size value (rE = 0.902; p < 0.001) then this result shows that the STEAM-based discovery learning model has a positive effect on students' critical thinking skills at high criteria. This finding shows that the application of the STEAM-based discovery learning model has a significant influence on students' critical thinking skills in learning at school.